DEVELOPING DIGITAL WORKSHEETS BY USING WIZER.ME FOR TEACHING VOCATIONAL SCHOOL IN MEDAN - Simarmata, Joy Jerrickson; Dewi, Nora Ronita (Universitas Negeri Medan, 2023)
This study aimed to develop an appropriate media for applying job chapter. This study was carried out at SMKS Karya Bunda Mandiri Medan. This research was conducted by using Research and Development (R&D) Method. The research of Research and Development contained six stages; gathering information and data, analyzing data, designing the material, validating by the experts, revising material, and creating the last was the final product. The data was gathered by distributing questionnaires to students and interviewing an English teacher to get the students' needs. The study's conclusion resulted in developing the Interactive E-Book, which may be used as a teaching medium for students to learn writing descriptive text. The product has been validated by two experts in percentage terms; the average score of expert validations was 87.6% in the content aspect, the presentation aspect was 84.9%, the language aspect was 90.6%, and the layout was 90%. The average score was 88.275% which was categorized as very good, and it was suggested to use it in English class, especially for applying for job chapters at the Vocational School level.